Impact of thyroid surgery volume and pathologic detection on risk of thyroid cancer: A geographical analysis in the Rhône‐Alpes region of France. (11th September 2018) - Hafdi‐Nejjari, Zakia; Abbas‐Chorfa, Fatima; Decaussin‐Petrucci, Myriam; Berger, Nicole; Couray‐Targe, Sandrine; Schott, Anne‐Marie; Sturm, Nathalie; Dumollard, Jean Marc; Roux, Jean Jacques; Beschet, Isabelle; Colonna, Marc; Delafosse, Patricia; et al.
Summary: Objective: To investigate the impact of the volume of thyroid surgery and pathologic detection on the risk of thyroid cancer. Methods: We investigated the influence of the volume of thyroid surgery in a first study that included 23 384 thyroid surgeries and 5302 thyroid cancers collected between 2008 and 2013. Standardized incidence ratios (SIRs) and thyroid intervention rates (STIRs) were used as indicators of cancer risk and surgery volume, respectively. The influence of pathologic detection, using the number of cuts per gram of tissue as the indicator, was studied in a second study that included 1257 thyroid specimens, collected in 2014. Results: We found departmental variations in SIRs and a significant effect of the STIR on the SIR (men, P = 0.0008; women, P < 0.0001). A 1/100 000 increase in the STIR resulted in a 3% and 1.3% increase in the SIR in men and women, respectively. This effect was greatest for microcancers and absent for tumours >4 cm. The risk of cancer diagnosis was significantly associated with the number of cuts per gram of tissue (OR 6.1, P < 0.001), and was greater for total thyroidectomy than for lobectomy ( P = 0.014) and when FNA cytology had been preoperatively performed ( P < 0.001). The prevalence of incidental microcancers was highest in the centres performing the highest number of cuts per gram. Conclusions: The risk of thyroid cancer, particularly microcancer, is related to the volume of surgery and to the level of pathologist scrutiny. Both factors contribute to the increase in overdiagnosis. This further advocates for appropriate selection of patients for thyroid surgery.